Microflora of Soil as Viewed by Freeze-Etching - Balkwill, D. L. (1973)
The indigenous microflora of soil were released from the soil materials and concentrated without the occurrence of growth by use of a blending-simple centrifugation procedure. The cell concentrate was then frozen-etched and viewed by transmission electron microscopy. Criteria were established for detecting microbial cells among the residual soil debris. The freeze-etching of the soil cell concentrate provided results on cell size distributions in agreement with those obtained by thin sectioning. However, the blending-simple centrifugation procedure for cell release and concentration from soil allowed the observation of large cells (≥1.0 μm in diameter) which apparently are missed by the “exhaustive centrifugal washing” cell separation-concentration procedure. The procedure of blending-simple centrifugation combined with the viewing of frozenetched preparations allowed evaluations of the soil microflora for cellular diameters, length-width ratios, shapes, and structure.